THE EFFECT OF SELF-EFFICACY, CLASSROOM CIMATE, AND PARENTAL SUPPORT ON STUDENTS’ MOTIVATION IN LEARNING ECONOMICS - Sahira, Alya Nur Sahira; Octoria, Dini Octoria; Sari, Dhany Efita; Ahmad, Noor Lela (Universitas Muhammadiyah Surakarta, 2025)
This study aimed to examine: (1) the effect of self-efficacy on students’ motivation in learning economics, (2) the effect of classroom climate on students’ motivation in learning economics, (3) the effect of parental support on students’ motivation in learning economics, and (4) the effect of self-efficacy, classroom climate, and parental support on students’ motivation in learning economics. The research was based on observed phenomena and previous studies related to students’ motivation in learning economics. A quantitative descriptive approach was used, with a sample of 242 students selected using the proportionate random sampling technique. Data were collected through questionnaires using a likert scale and analyzed using assumption tests and hypothesis testing, including t-tests and F-tests. The results of the study showed that self-efficacy, classroom climate, and parental support had a positive and significant influence of 91,2% on students’ motivation in learning economics. Further analysis using multiple linear regression indicated that each independent variable partially had a significant effect on learning motivation, while simultaneously the three variables contributed substantially to the explained variance in students’ motivation. These findings suggest that efforts to enhance students’ self-efficacy, create a supportive classroom climate, and strengthen parental involvement are essential to improve students’ motivation in learning economics and should be considered in the development of effective educational strategies.